The Challenges Of Assunta Hospital In Facing Competition Locally And Globally - Rajagopal, Gobindran Raj (2008)
Started by four Franciscan Missionaries of Mary (FMM) sisters Assunta started off as being a community service based organization, with its main objective to help the poor and needy. It started operating from single storey house an expanded amazingly to a complete medical center within the time span of 15 years.